ЕКСПРЕСІЯ ALU-ПОВТОРІВ У ПЛАЗМІ КРОВІ ХВОРИХ НА РАК МОЛОЧНОЇ ЗАЛОЗИ В ПРОЦЕСІ НЕОАД’ЮВАНТНОЇ ХІМІОТЕРАПІЇ: ПОШУКОВЕ ДОСЛІДЖЕННЯ - Özgür, E.; Ferhatoglu, F.; Sen, F.; Saip, P.; Gezer, U. (PH Akademperiodyka, 2023)
Background:Locally advanced breast cancer (LABC) rates are unusually high in developing countries. There is a need for the identification of predictive biomarkers for the selection of patients who could benefit from neoadjuvant chemotherapy (NAC). Aim: As the expression of ALU repeat is increased in cancer and has not been assessed in liquid biopsy of cancer patients, our goal was to assess ALU expression in the blood plasma of LABC patients during NAC. Patients and Methods:Plasma samples drawn at baseline and at the end of the fourth cycle of chemotherapy were used to determine the plasma levels of ALU-RNA by quantitative real-time PCR. Results: ALU expression from baseline to the fourth cycle of NAC increased from a median relative level of 1870 to 3370 in the whole group (p = 0.03). The increase in ALU-RNA levels in the course of NAC was more pronounced in premenopausal women and in patients with hormone-positive tumors. In patients with complete response to NAC, baseline ALU expression was higher than that in those with partial response. Conclusion: This exploratory study provides evidence that plasma ALU-RNA levels are modulated by the menopausal status and hormone receptor status of breast cancer patients and pre-therapeutic ALU-RNA levels might be useful in predicting the response to chemotherapy in a neoadjuvant setting.